FREQUENCY SYMBOLIC METHOD OF ASSESSMENT OF ASYMPTOTIC STABILITY OF LINEAR TIME-VARIABLE CIRCUITS - Shapovalov, Yuriy; Mandziу Bohdan; Smal, Dariya (International Journal of Computing, 2014)
The method of assessment of asymptotic stability of linear time-variable circuits by frequency symbolic approach is considered in this paper. The method consists of the replacing in criteria of stability the necessity of formation of bifrequency transfer function of circuit on the formation of a normal parametric transfer function in its inertial part. This leads to significant simplification of the method of assessment of a stability.